2018
DOI: 10.1097/tp.0000000000002224
|View full text |Cite
|
Sign up to set email alerts
|

T Follicular Regulatory Cells and Antibody Responses in Transplantation

Abstract: De novo donor-specific antibody (DSA) formation is a major problem in transplantation, and associated with long-term graft decline and loss as well as sensitization, limiting future transplant options. Forming high-affinity, long-lived antibody responses involves a process called the germinal center (GC) reaction, and requires interaction between several cell types, including GC B cells, T follicular helper (Tfh) and T follicular regulatory (Tfr) cells. T follicular regulatory cells are an essential component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 161 publications
(194 reference statements)
0
20
0
Order By: Relevance
“…In addition, Foxp3 acts as a marker for regulatory T cells (Tregs) and has a protective effect on infiltration in immune organs. Foxp3+ T follicular regulatory cells (Tfrs) have recently been found to inhibit the onset of ABMR promoted by Tfh cells ( 47 , 48 ). The upregulation of splenic Foxp3 in the Allo+Combination group also revealed a possible alteration in regulatory T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Foxp3 acts as a marker for regulatory T cells (Tregs) and has a protective effect on infiltration in immune organs. Foxp3+ T follicular regulatory cells (Tfrs) have recently been found to inhibit the onset of ABMR promoted by Tfh cells ( 47 , 48 ). The upregulation of splenic Foxp3 in the Allo+Combination group also revealed a possible alteration in regulatory T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Tfr cells are believed to induce the inability of Tfh cells in the GC, specifically preventing incessant antibody-produced B cell responses. Subsequent evidence suggested that Tfr cells effectively regulated humoral immune responses in autoimmune diseases and organ transplantation 19,[56][57][58][59] . A leading theory is that Tfr cells are formidable adversaries against chronic graft-versus-host diseases (cGVHD) 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…The GC response is regulated by follicular regulatory T (Tfr) cells which are a subset of regulatory T cells (Tregs) [42,43]. Tfr cells share markers with both Tregs and Tfh cells [44,45] and recent studies suggest that they might perform their suppressive function not only inside the GC but also from the outside in [46]. Both pretransplant and dnDSA of the IgG class are strongly associated with acute and chronic allograft injury which suggests that GC reactions are crucial in the pathophysiology of ABMR in kidney transplant patients [47,48].…”
Section: Cellular Mechanism Of Action Of Tacrolimus In Dndsa Developmmentioning
confidence: 99%